Nature Integration in the Elementary Classroom - Tilden, Emily L. (My University, 2017)
Integrating nature into the elementary classroom is beneficial to the students academically and behaviorally. Because of this, I have created a series of lesson plans that immerse students in nature as they learn material. These lesson plans are based off of the research presented in the beginning of this project. There are lesson plans in all content areas to show that nature integration is cross-curricular. Additionally, there are resources for productive play involving natural elements. I facilitated the ELA lesson in a 4th grade classroom where I found that the interaction with nature lead to creative and focused responses in student writing and class discussion. I have also included an ecological art project that hopes to begin conversations about the lack of interaction modern-day humans have with the Earth. As educators, it is necessary to be aware of how time outside positively effects our students. If students do not know our planet, we cannot expect them to work to help it. Interaction with natural elements benefits students emotionally, academically, and physically. When educators bring nature into the classroom, or bring the classroom to nature, they help create a generation that knows and cares for their planet.